Overview on Lithium-Ion Battery 3D-Printing By Means of Material Extrusion. (8th September 2020) - Maurel, Alexis; Grugeon, Sylvie; Armand, Michel; Fleutot, Benoit; Courty, Matthieu; Prashantha, Kalappa; Davoisne, Carine; Tortajada, Hugues; Panier, Stéphane; Dupont, Loic
Abstract : Among the various additive manufacturing processes, material extrusion techniques recently emerged as an encouraging option in order to 3D-print lithium-ion battery components. In this work, an overview of the recent advances and progress on the ink material extrusion, known as liquid deposition modeling (LDM), as well as the thermoplastic material extrusion process, known originally as the trademark Fused Deposition Modeling (FDM), is discussed. Representing a promising route to achieve complete lithium-ion batteries in a single print without the necessity to perform any post-processes, a particular consideration is devoted to the FDM process. Trends, prospects as well as an exhaustive list of the parameters still requiring further investigations are provided, thus paving the way towards the next generation of FDM 3D-printed lithium-ion batteries.